(untitled) (Acta Entomologica Serbica, 2010)
The material of Aspicera collected from Iran has shown that Aspicera abbreviata Belizin 1952 is an aberrant form of A. tobiasi Belizin, 1961. Aspicera abbreviata is redescribed and A. tobiasi is synonymized with A. abbreviata. The morphological differences between this species and the other members of the genus are given, and its most important characters are illustrated. The male of A. abbreviata is described for the first time. This species has been recorded for the first time in Iran.